Noninvasive continuous blood pressure monitoring using microelectromechanical system technology. Issue 3 (June 2019) - Satake, Shuichi; Shimura, Tatsuo; Ono, Tetsuya; Shimomura, Kenju; Takenoshita, Seiichi; Kono, Koji
Abstract : Background: Continuous blood pressure monitoring is essential in the management of patients in critical conditions, as well as those under anesthesia. However, continuous blood pressure monitoring requires insertion of a catheter into the radial artery. Thus, continuous noninvasive arterial blood pressure monitoring would be ideal. Participants and methods: We designed and built a continuous noninvasive arterial blood pressure monitoring device with a pressure sensor diaphragm using microelectromechanical system technology, a square with 4 mm sides that were 0.4 mm thick. Comparisons between a continuous noninvasive arterial blood pressure monitoring device and a sphygmomanometer were carried out on 92 volunteers, and comparisons between noninvasive and invasive blood pressure monitoring were performed on three patients perioperatively at Fukushima Medical University Hospital. Results: In the comparisons of arterial blood pressure measurements between a sphygmomanometer and our device, the differences became gradually greater over time after starting continuous monitoring in conscious participants. In the comparisons of arterial blood pressure measurements between the invasive and noninvasive methods in unconscious subjects under general anesthesia, the results of noninvasive monitoring were consistent with those of invasive arterial blood pressure monitoring. Conclusion: Continuous noninvasive arterial monitoring with a pressure sensor diaphragm using microelectromechanical system technology is a possible alternative to conventional invasive arterial pressure monitoring by an arterial catheter.